Crop coefficients and actual evapo-transpiration of gram (Cicer arietinum) grown in lysimeter - JADHAV, J D; SHEWALE, M R; MOKASHI, D D; GAIKWAD, C B; PATIL, J D (The Indian Journal of Agricultural Sciences, 2013)
A rainfed experiment was conducted during 1988-89 to 1993-94 to study the evapo-transpiration (ET) loss, identify the peak periods of consumption of water and the critical period of life-saving irrigation in gram or chickpea (Cicer arietinum L.) grown in a Iysimeter. Weekly crop-coefficient values and evapo-transpiration. Pan evaporation (PE) ratios were also calculated. The mean seasonal evapo-transpiration of the crop was 185 mm. The ET : Eo ratio and Kc values increased with increase in crop growth and reached a maximum during 36-70 days of the crop growth, which was the critical period for water demand that decreased as the crop approached maturity. The most critical period for water demand was flowering stage. The mean moisture-use efficiency was 33 kg/ha/mm under rainfed condition.